Proposal of an evaluation model for mental health care networks by using information technologies for its management - Vinci, André Luiz Teixeira (2020)
Abstract: Mental health is an integral part of people\'s health and well-being, but, in many countries, policies and legislation are not widely developed enough to include all the people with mental health problems and their families. In 2011, the Unified Health System (SUS) established the Psychosocial Care Networks (RAPS) in Brazil. However, no standardized procedures or indicators for the evaluation and management of RAPS were identified or established in the Brazilian legislation. Therefore, this study aims to propose and validate an evaluation model for municipal and regional management of a mental health care networks (RAPS). This model should consider the understanding of the professionals responsible for the municipal and regional management of the network as well as the used information systems and the indicators identified in the literature and / or used in network management, by also using the XIII Regional Health Department (DRS XIII) of São Paulo state as a field of study. From the proposed evaluation model, we carry out the development and validation of an instrument for semi-structured interviews to identify practices, needs and perceptions within the scope of mental health management between health managers and mental health care articulation technicians at regional and municipal level. This instrument was applied to health managers and mental health technicians (n = 43) in the study region and obtained information about legislation, decision-making processes, network structure, management participants, information systems, indicators, and knowledge of external experiences. In addition, we proposed a set of 49 mental health indicators that can be measure with the current information systems in Brazil and obtained through knowledge extraction from scientific literature and other sources. Thus, we proposed a prototype tool to supply indicators in a web information system in order to provide relevant information for network management in an agile way. Finally, in addition to the main study results, the use of the proposed model in any specific localities will enable the growth in mental health knowledge by the network\'s stakeholders and patients as well as the improvement on the quality of the health care and management in the region, with a strong academic content.